TLR9-JNK signaling pathway regulates hypoxia-induced proliferation of rat pulmonary artery smooth muscle cells - WU Qijian; WU Qijian; ZHANG Erlong; ZHANG Erlong; SUN Binda; SUN Binda (Di-san junyi daxue xuebao, 2021)
Objective To investigate the role and mechanism of Toll-like receptor 9 (TLR9) in hypoxia-induced proliferation of rat pulmonary artery smooth muscle cells (RPASMCs). Methods MTT assay, Western blotting and PCR were adopted to measure cell proliferation level, protein and mRNA levels of following molecules in RPASMCs. ① After RPASMCs were treated with 3% O2 for 36 h to establish a hypoxic model, the cell proliferation and expression levels of TLR9 and phosphorylated c-jun N-terminal kinase(p-JNK) were detected at the same time. ② After TLR9 was knocked down using small interfering RNA sequence (siRNA) or activated by 20 μmol/L TLR9 agonist, ODN 1826, under hypoxia, the proliferation and p-JNK level were examined. ③RPASMCs were treated with 5 μmol/L JNK inhibitor SP600125 under hypoxia, and the proliferation was assayed. ④ Under hypoxia, 20 μmol/L ODN 1826 combined with 5 μmol/L SP600125 were administered to RPASMCs, and the proliferation and level of p-JNK were measured. Results The proliferation of RPASMCs (1.30±0.07, P < 0.01) and protein levels of TLR9 (1.70±0.22, P < 0.05) and p-JNK (1.83±0.18, P < 0.01) were significantly higher in the hypoxia group than the normoxia group. Knock-down of TLR9 significantly inhibited hypoxia-induced proliferation of RPASMC (0.64±0.09, P < 0.01) and reduced the JNK phosphorylation (0.49±0.01, P < 0.001). TLR9 agonist, ODN 1826, significantly promoted the proliferation of RPASMCs (2.01±0.08, P < 0.001) and increased JNK phosphorylation (2.11±0.33, P < 0.01). JNK inhibitor SP600125 inhibited the proliferation (0.70±0.06, P < 0.05). Compared with hypoxia+TLR9 agonist group, the level of p-JNK (0.82±0.14 vs 1.59±0.30, P < 0.001) and cell proliferation (1.08±0.05 vs 1.35±0.02, P < 0.001) were both decreased significantly in hypoxia+TLR9 agonist+JNK inhibitor group. Conclusion TLR9 promotes the proliferation of RPASMCs by activating the JNK pathway under hypoxia.